Energy Storage: Bilayer Structure with Ultrahigh Energy/Power Density Using Hybrid Sol–Gel Dielectric and Charge‐Blocking Monolayer (Adv. Energy Mater. 19/2015). Issue 19 (October 2015) - Kim, Yunsang; Kathaperumal, Mohanalingam; Chen, Vincent W.; Park, Yohan; Fuentes‐Hernandez, Canek; Pan, Ming‐Jen; Kippelen, Bernard; Perry, Joseph W.
<x xml:space="preserve">Abstract</x> A bilayer dielectric material showing remarkable energy/power density is reported in article number 1500767 by Joseph Perry and co‐workers. This material has been developed through the use of an organic‐hybrid sol‐gel dielectric layer and a self‐assembled‐monolayer as a charge‐blocking layer, which greatly suppresses current leakage at high electric field. This hybrid energy‐storage device provides an energy density of 40 J cm−3. In the cover image luminous dots represent charges and the amorphous sol‐gel layer is below the monolayer.